2019
DOI: 10.4103/jmh.jmh_128_18
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological correlation of international federation of gynecology and obstetrics's PALM–COEIN classification of abnormal uterine bleeding: Indian scenario

Abstract: Background:Abnormal uterine bleeding (AUB) is a common problem affecting the women of reproductive age group and may also have a significant impact on their physical, social, and emotional aspects directly affecting their quality of life. The International Federation of Gynecology and Obstetrics (FIGO) devised a universally acceptable system of nomenclature and classification, namely PALM–COEIN classification of AUB in the year 2011. The objective of the present study was to analyze the structural (PALM) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
4
6
0
Order By: Relevance
“…Overall histopathology detected more polyps but the difference was not statistically significant. Our findings were similar to other such studies [12,13].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Overall histopathology detected more polyps but the difference was not statistically significant. Our findings were similar to other such studies [12,13].…”
Section: Discussionsupporting
confidence: 94%
“…As compared to clinical diagnosis, histopathological examination detected structural abnormalities in more cases (529 vs 570 out of 702 cases) which was statistically significant too. Similar studies analysing clinicopathological correlation found histopathology detecting more structural pathologies than clinically suspected 13]. This was majorly due to additional histological detection of adenomyosis, coexistent dual structural pathologies like missed leiomyomas, polyps and premalignant cervical lesions.…”
Section: Discussionsupporting
confidence: 55%
“…Most of the scientists prefer the new classification of causes of AUB (PALM-COEIN) which takes into account the etiological factor 8,9,10…”
Section: Discussionmentioning
confidence: 99%
“…Since the revision of the FIGO classification of AUB in 2018, reports on the incidence of each causative disease in PALM-COEIN 1,8,9,[12][13][14] and the relationship with ultrasound findings and pathology results in PALM-COEIN have mainly been reported using system 2. [15][16][17][18] In addition, some reviews explored biomarkers that may be useful in the diagnosis of AUB for each causative disease of AUB, 19 and most of the reports have discussed how to accurately diagnose the causative disease of AUB using PALM-COEIN. However, to the best of our knowledge, there have been no reports on the symptoms of AUB using system 1 or on the relationship between system 1 and system 2.…”
Section: Discussionmentioning
confidence: 99%